2013
DOI: 10.1001/jamaophthalmol.2013.4382
|View full text |Cite
|
Sign up to set email alerts
|

Visual Field Progression With Frequency-Doubling Matrix Perimetry and Standard Automated Perimetry in Patients With Glaucoma and in Healthy Controls

Abstract: IMPORTANCE A new analysis method called permutation of pointwise linear regression measures the significance of deterioration over time at each visual field location, combines the significance values into an overall statistic, and then determines the likelihood of change in the visual field. Because the outcome is a single P value, individualized to that specific visual field and independent of the scale of the original measurement, the method is well suited for comparing techniques with different stimuli and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
(28 reference statements)
1
22
0
Order By: Relevance
“…In glaucoma suspects, Meira-Freitas et al (2014) reported that faster rates of increase of FDT pattern deviation were related to higher chance of progression in SAP, and Liu et al (2014b) reported that approximately the same number of suspects developed reproducible defects in FDT or in SAP. In glaucoma patients, Liu et al (2014a) identified more progressing patients with FDT than SAP; however, Redmond et al (2013) identified more progressing patients with SAP than FDT. While some studies suggest that FDT may be useful to evaluate progression of glaucoma functional damage, further research is required to better assess its additional value to SAP, before recommending frequent clinical use.…”
Section: Frequency-doubling Technology Perimetrymentioning
confidence: 91%
“…In glaucoma suspects, Meira-Freitas et al (2014) reported that faster rates of increase of FDT pattern deviation were related to higher chance of progression in SAP, and Liu et al (2014b) reported that approximately the same number of suspects developed reproducible defects in FDT or in SAP. In glaucoma patients, Liu et al (2014a) identified more progressing patients with FDT than SAP; however, Redmond et al (2013) identified more progressing patients with SAP than FDT. While some studies suggest that FDT may be useful to evaluate progression of glaucoma functional damage, further research is required to better assess its additional value to SAP, before recommending frequent clinical use.…”
Section: Frequency-doubling Technology Perimetrymentioning
confidence: 91%
“…Redmond and coworkers13 using PoPLR found HFA SAP detected progression in about twice as many subjects as FDT2 but far more normal subjects were identified as progressing with HFA SAP. Hu et al found no benefit of FDT2 over HFA SAP in monitoring glaucoma progression.…”
Section: Discussionmentioning
confidence: 98%
“…Using FDT2, Redmond and coworkers13 studied 64 subjects with primary open angle glaucoma and 36 controls. Subjects were tested every 6 months with FDT2 and HFA SAP using the 24–2 pattern on the same day.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in a cohort of glaucoma subjects and normal controls monitored for a median of about 5 years, progression was identified in fewer glaucoma patients with FDT compared with SAP using permutation analyses of PLR of either total deviation or pattern deviation data [25]. About one-third of control subjects were identified as having deterioration with SAP, using total deviation data, but in only 8 % with FDT.…”
Section: Frequency Doubling Technology Perimetrymentioning
confidence: 95%